Sleep disturbances, sleep quality, and cardiovascular risk factors in women with polycystic ovary syndrome: Systematic review and meta-analysis - Zhang, Jiayu; Ye, Jiawen; Tao, Xinge; Lu, Wenjing; Chen, Xueqin; Liu, Changqin (Frontiers in Endocrinology, 2022)
Objectives: (1) To establish the prevalence of sleep disorders in women with PCOS. (2) To establish the association between sleep disturbance and cardiovascular risk factors in women with PCOS. Methods: The electronic databases PubMed and EMBASE were searched for observational studies of individuals with PCOS published in English from inception to October 21, 2021. The dichotomous outcome measure was presented as odds ratio (OR) and 95% confidence interval (CI). The mean difference (MD) in continuous variables was expressed for each study. Results: Totally, 18 articles were included in this meta-analysis, with a total of 16152 participants from 9 different countries. Women with PCOS had a high prevalence of sleep disturbance (OR=6.22; 95% CI: 2.77, 13.97; P<0.001), higher PSQI scores (MD=2.10; 95% CI 0.29, 3.90; p =0.02) and shorter duration of sleep (MD=-15.65min; 95% CI=-27.18, -4.13; P=0.008). We found that body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), low-density lipoprotein cholesterol (LDL-c), fasting glucose, 2-h glucose, waist circumference (WC) levels were significantly higher and high-density lipoprotein cholesterol (HDL-c) was significantly lower in PCOS with sleep disturbance than in PCOS without sleep disturbance. Conclusions: The current study shows a high prevalence of sleep disturbance in women with PCOS and provides evidence of an association between cardiovascular risk factors and sleep disturbance among this population. Increased attention should be paid to sleep management in clinical guidelines for PCOS. Systematic review registration: PROSPERO [https://www.crd.york.ac.uk/PROSPERO/], identifier CRD42022298040.